23 Long-term follow-up in transient epileptic amnesia: prognosis over 10–20 years. Issue 8 (13th July 2017) - Savage, Sharon A; Butler, Christopher R; Baker, John; Hodges, John R; Zeman, Adam Z
Abstract : Objective: Transient Epileptic Amnesia (TEA) is a form of adult onset temporal lobe epilepsy characterised by ictal amnesia, which is often accompanied by interictally memory disturbances of autobiographical amnesia and accelerated long-term forgetting. Short-term follow-up studies conducted 1–2 years after commencing anticonvulsant therapy, suggest good seizure control, together with a relatively stable cognitive profile. Recent case reports, however, have raised concerns regarding a risk of developing Alzheimer's Disease (AD). This paper reports on the clinical and cognitive outcome of TEA patients over a 10 to 20 year period. Method: Two cohorts of TEA participants were studied at 10 year intervals: an initial cohort of 10 patients (C1), followed up at 10 and 20 years; and an additional 42 patients (C2), followed up at 10 years only. Information regarding clinical outcomes (mortality, seizure history and subjective reports of memory functioning) was gained via GP records and clinical interview. Objective memory function was determined at each time point via a comprehensive neuropsychological assessment, where possible. Results were compared with age-matched healthy control participants. Results: Information was available for 9 patients from C1 (90%), and 37 (88%) from C2. In C1, 4 participants (40%) had died over the 20 year period, with no indication of dementia prior to death (mean age at death =82 years). One participant was diagnosed with Vascular Dementia. In C2, 15 participants (40%) had died, including one patient with AD (mean age of death =81 years). Dementia was diagnosed in a further 5 patients (3 with AD). Seizures were generally well controlled in both cohorts. Subjective memory complaints were significantly greater in TEA patients than matched controls, although reports varied in both C1 and C2, ranging from no concerns through to either stable memory difficulties, or worsening memory. Neuropsychological assessment showed no evidence of a general cognitive decline at either the 10- or the20-year follow up, with TEA participants performed similarly to healthy controls on the majority of standard neuropsychological tests. Within the memory domain, both TEA cohorts included patients with stable memory performance over time relative to healthy controls, as well as those showing impairments on one or more memory measures. Additional impairments in other cognitive domains (typically executive function) were observed in some patients. Conclusion: Despite concerns raised regarding dementia, the prognosis of TEA appears relatively benign. While persistent memory difficulties are a common outcome, the prevalence of dementia in TEA does not exceed population prevalence data.